Faktor-faktor yang Mempengaruhi Indeks Pembangunan Manusia Sumatera Barat - Amelia, Dona (Jurnal Ekonomi, 2013)
The Human Development Index (HDI) is a summary composite index that measures a country's average achievements in three basic aspect of human development: health, knowledge, and income. HDI was introduced as an alternative to conventional measures of national development, such as level of and the rate of economic growth. The HDI measures in the three basic dimensions-health, knowledge and income. The HDI formula, health was measure by life expectancy at birth; education or "knowledge" by a combination of the adult literacy rate and school enrolement rates (for primary through university years); and income or standart of living by GDP per capita adjusted for puschasing-power parity (PPPUS$). For West Sumatera, showing positive progress of HDI attainment, however since 2004-2010 there was a stagnant rank nationally at the number 9 position of its HDI. There are four independent variable as determinant HDI in this research namely: income per capita, government expenditure for health and education, poverly rate and child mortality. Several treatmenr of statistical regression analysis of the these four variables showing different result. The best result showed by HDI = 69,929+0,001 IPC-0,001 KE-0,150 AKB. The F test value is 21,603, significant at a 1%. The R2 is 0,812 which mean 81,30% of HDI variation can be explained by income per capita, poverty rate and child mortality.